Analysis of Mathematical Reasoning Ability of Eight Grade on CORE Learning Model in terms of Thinking Style (Unnes Journal of Mathematics Education, 2022)
This study aimed to determine the effectiveness of the CORE learning model toward students’ mathematical reasoning ability and describe the students’ mathematical reasoning ability through the application of the CORE learning model in terms of students’ thinking styles. This study used a mixed method with a concurrent embedded strategy and posttest-only control group design. The population in this study were the eight grade students of SMP Negeri 2 Patebon. Samples were taken by using a simple random technique and obtained VIII A class as an experimental and VIII C as a control class. Subjects of this study were determined by using the purposive technique and obtained two students from each thinking style category. Data collection techniques in this study were a test, questionnaire, interview, and documentation. The quantitative data analysis of this study used both initial and research data. Research data analysis consists of individual completeness tests, classical completeness tests, average difference tests, and proportional difference tests. Before testing the effectiveness of learning, the prerequisite test is conducted first, namely the normality and homogeneity test. The qualitative data analysis technique was carried out by using qualitative descriptive methods, including data reduction, data display, and conclusion drawing. The results showed that (1) the implementation of the CORE learning model is effective towards students’ mathematical reasoning ability; and (2) subject with concrete sequential have good ability in mathematical reasoning; subject with abstract sequential tends to be very good in mathematical reasoning ability; subject with concrete random tends to be good in mathematical reasoning ability; subject with abstract random tends to have the low ability in mathematical reasoning.